1998
DOI: 10.1007/s11663-998-0059-1
|View full text |Cite
|
Sign up to set email alerts
|

Liquid flow on a rotating disk prior to centrifugal atomization and spray deposition

Abstract: Video observations of the flow patterns that develop on a rotating disk during centrifugal atomization and spray deposition, and subsequent metallographic studies conducted on solid skulls removed from the disk after processing, have indicated a circular discontinuity or hydraulic jump, which is manifested by a rapid increase in the thickness of the liquid metal and by a corresponding decrease in the radial velocity. A mathematical model has been developed that is capable of predicting both the occurrence and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 15 publications
0
19
0
Order By: Relevance
“…Some analyses on the liquid flow on a rotating disk were carried out by a numerical simulation. The description of the numerical approach is not included here and the interested reader is referred to the literatures, for example, [26,27]. Here, we resort to the same approach.…”
Section: Validity Of the Assumptionsmentioning
confidence: 99%
“…Some analyses on the liquid flow on a rotating disk were carried out by a numerical simulation. The description of the numerical approach is not included here and the interested reader is referred to the literatures, for example, [26,27]. Here, we resort to the same approach.…”
Section: Validity Of the Assumptionsmentioning
confidence: 99%
“…(2), for each phase. (2) where, apart from the conventional symbols (see NOMENCLATURE), F a is an additional momentum source accounting for surface tension at the free surface that is approximated by using the Continuum Surface Force method of Brackbill et al [13]; and C αβ is the interphase drag force calculated using a free surface approach described by Eq. (3) [11]: 3where and C D = 0.44.…”
Section: Governing Equationsmentioning
confidence: 99%
“…Emslie et al [1] utilised a method of characteristic curves to demonstrate that a film with an initial irregular fluid distribution develops towards a uniform distribution under centrifugal effect. Zhao et al [2] conducted experimental work to visualise the flow of liquid metal on a spinning disc and observed that for their operating conditions a hydraulic jump formed at a radial distance, depending on the liquid kinematic viscosity, the volume flow rate, the hydrostatic head of feeding stream, and the disc spinning speed, resulting in a sudden increase in film thickness. An analytical model was developed by Zhao et al [2] that described the flow of a liquid film on the spinning disc and predicted the occurrence and location of the hydraulic jump.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the complexity of melt flow on an atomization disk and the speed of the disk edge, the atomization mode on the disk edge is difficult to identify as a specific mode without clear high speed image [5]. Therefore, mathematical models based on the flow behavior of liquid melt must be experimentally verified before they can be relied upon to predict particle shape and particle size distribution [5,9]. Ideally, centrifugally atomized powders have an approximately spherical shape.…”
Section: Atomization Modesmentioning
confidence: 99%